Enhanced carrier collection efficiency of GeSn single quantum well towards all-group-IV photonics applications. (28th July 2022) - Olorunsola, Oluwatobi; Said, Abdulla; Ojo, Solomon; Abernathy, Grey; Saha, Samir; Wangila, Emmanuel; Grant, Joshua; Stanchu, Hryhorii; Acharya, Sudip; Du, Wei; Jheng, Yue-Tong; Chang, Guo-En; et al.
Abstract: GeSn-based quantum wells (QWs) are of great interests for the development of all-group-IV optoelectronic devices such as lasers. Using a GeSn buffer and SiGeSn barrier has been studied with the aim of obtaining a direct bandgap well and increasing the carrier confinement. However, the carrier collection efficiency with such a configuration remains unsatisfactory. In this work, a single QW with additional GeSn barrier inserted between the GeSn well and the SiGeSn barrier was grown and characterized. Under relatively low carrier injection, the photoluminescence results show dramatically enhanced emission from the QW compared to the reference samples with only SiGeSn barrier, indicating a significantly improved carrier collection efficiency of the well.